CLINICO-PATHOLOGICAL PROFILE AND OUTCOMES OF PATIENTS WITH POLYCYTHAEMIA VERA, ESSENTIAL THROMBOCYTHAEMIA AND IDIOPATHIC MYELOFIBROSIS: A TERTIARY CARE CENTER EXPERIENCE FROM SOUTHERN PAKISTAN - Shaikh, Muhammad Shariq; Shaikh, Mohammad Usman; Adil, Salman Naseem; Khurshid, Mohammad; Ahmed, Zeeshan Ansar (Journal of Ayub Medical College Abbottabad, 2016)
Background: The Philadelphia Negative Classic Myeloproliferative Neoplasms include polycythaemia vera (PV), essential thrombocythaemia (ET) and idiopathic myelofibrosis (IMF). These three disorders share several clinical and laboratory features including JAK2 V617F mutation. Our objectives were to determine the clinico-pathological profile and outcomes of Pakistani patients with polycythaemia vera (PV), essential thrombocythaemia (ET) and idiopathic myelofibrosis (IMF) in order to have an insight regarding behaviour of these conditions. Methods: A retrospective analysis of all the cases of PV, ET and IMF diagnosed at our institute from January 1995 to December 2013 was performed. Age, gender, clinical presentation, laboratory investigations, treatment provided and duration of follow-up were included for analysis. Appropriate statistics were utilized for calculation of data. Results: A total of 58 patients were diagnosed as PV, ET or IMF during the study period. Male to female ratio was 1.1:1. Forty five percent (n=27) patients came to medical attention due to abnormal laboratory results, 3 had cerebrovascular events, 3 had pruritus, and 1 patient each with gangrene and Budd-Chiari syndrome. Haemorrhage was not seen in any patient. Sixty percent (n=35) patients were treated with phlebotomy, hydroxyurea and aspirin alone or in combination. None of the patients transformed to myelofibrosis (MF) or myelodysplasia (MDS) during the mean (±SD) follow-up period of 57.2±50 months. One patient with ET transformed to acute myeloid leukaemia 9 years after the diagnosis. Conclusions: This study demonstrated a relatively more benign form of PV, ET and IMF with lesser frequency of symptoms, good response to treatment and less likelihood of transformation to MF, MDS or AML. Keywords: Myeloproliferative neoplasms, Polycythaemia vera, Essential thrombocythaemia, Idiopathic myelofibrosis, Pakistan